2006
DOI: 10.7249/mg480
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mathematics and Science Education: A Longitudinal Investigation of the Relationship Between Reform-Oriented Instruction and Student Achievement

Abstract: This document and trademark(s) contained herein are protected by law as indicated in a notice appearing later in this work. This electronic representation of RAND intellectual property is provided for noncommercial use only. Permission is required from RAND to reproduce, or reuse in another form, any of our research documents. The RAND Corporation is a nonprofit research organization providing objective analysis and effective solutions that address the challenges facing the public and private sectors around th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Previous investigations in both reading (Foorman et al, 2006; Xue & Meisels, 2004) and mathematics (Desimone & Long, 2010; Guarino et al, 2013; Le et al, 2006; Palardy & Rumberger, 2008) have also observed associations between a classroom teacher’s instructional practices and children’s academic achievement. For example, Xue and Meisels’ effect size estimates for whole language- and phonics-type instruction were .08 and .06, respectively, about the same magnitudes we found for the effects of teacher-directed instruction on the two lowest-performing groups of students.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Previous investigations in both reading (Foorman et al, 2006; Xue & Meisels, 2004) and mathematics (Desimone & Long, 2010; Guarino et al, 2013; Le et al, 2006; Palardy & Rumberger, 2008) have also observed associations between a classroom teacher’s instructional practices and children’s academic achievement. For example, Xue and Meisels’ effect size estimates for whole language- and phonics-type instruction were .08 and .06, respectively, about the same magnitudes we found for the effects of teacher-directed instruction on the two lowest-performing groups of students.…”
Section: Discussionmentioning
confidence: 86%
“…Doing so may have resulted in inflated effect size estimates. In addition, these studies have often been unable to control for prior mathematics achievement, socio-economic status (SES) and other potential confounds (e.g., Le et al, 2006). Despite constituting a “gateway grade,” as mathematics instruction becomes increasingly formal, Camburn and Han’s (2011) recent synthesis “turned up very little evidence on instruction in first grade” (p. 574), as only 10% of the included studies reported results from this grade level.…”
Section: The Extant Work’s Methodological and Substantive Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their exposure to more context-based problem solving situations better prepared them for open-ended responses. Years later, RAND extended this study with Mosaic II to include teaching observations and student learning measures over time (Le et al, 2006). Similar to first-year findings, Mosaic II showed a consistently positive but weak relationship between reformed teaching practices and student achievement.…”
Section: Literature Reviewmentioning
confidence: 56%